Greening spaces for worship and ministry : congregations, their buildings, and creation care - Torgerson, Mark Allen (Alban Institute, 2012)
Greening Spaces for Worship and Ministry is a comprehensive guide. The book provides a rationale, strategies, and resources for fulfilling environmental stewardship through the land and buildings of Christian and Jewish congregations. New construction, renovation, and historic preservation projects are addressed. Site development, material choices, energy generation and consumption, water use, interior air quality, green cleaning programs, and beauty are discussed. Ten congregations from across the United States and Canada are featured as e.